2018
DOI: 10.1002/acn3.688
|View full text |Cite
|
Sign up to set email alerts
|

Retinal image analytics detects white matter hyperintensities in healthy adults

Abstract: ObjectiveWe investigated whether an automatic retinal image analysis (ARIA) incorporating machine learning approach can identify asymptomatic older adults harboring high burden of white matter hyperintensities (WMH) using MRI as gold standard.MethodsIn this cross‐sectional study, we evaluated 180 community‐dwelling, stroke‐, and dementia‐free healthy subjects and performed ARIA by acquiring a nonmydriatic retinal fundus image. The primary outcome was the diagnostic performance of ARIA in detecting significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…From the initial search, 162 articles were retrieved with 38 of them being analyzed 19,21–57 . All included studies were prospective; five had an intraindividual study design with two 21,24,31,40 or three study groups 19 that were examined separately. In those cases, study groups were considered to be independent, resulting in a total of 44 study groups from the 38 articles.…”
Section: Resultsmentioning
confidence: 99%
“…From the initial search, 162 articles were retrieved with 38 of them being analyzed 19,21–57 . All included studies were prospective; five had an intraindividual study design with two 21,24,31,40 or three study groups 19 that were examined separately. In those cases, study groups were considered to be independent, resulting in a total of 44 study groups from the 38 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they concluded 59% hypertension, 26% hyperlipidemia and severe WMH of 36%. The correlation coefficient was of 0.897 [12].…”
Section: Literature Surveymentioning
confidence: 91%
“…[ 30 ] We recently showed that a retinal imaging analysis powered with machine learning technology achieved good performance in detecting CSVD in the community. [ 31 ]…”
Section: In Vivo Detectionmentioning
confidence: 99%